Enhancing global change experiments through integration of remote‐sensing techniques. Issue 4 (1st April 2019) - Shiklomanov, Alexey N; Bradley, Bethany A; Dahlin, Kyla M; M Fox, Andrew; Gough, Christopher M; Hoffman, Forrest M; M Middleton, Elizabeth; Serbin, Shawn P; Smallman, Luke; Smith, William K
Abstract : Global change experiments are often spatially and temporally limited because they are time‐ and labor‐intensive, and expensive to carry out. We describe how the incorporation of remote‐sensing techniques into global change experiments can complement traditional methods and provide additional information about system processes. We describe five emerging near‐surface remote‐sensing techniques: spectroscopy, thermal and fluorescence imaging, terrestrial laser scanning, digital repeat photography, and unmanned aerial systems. The addition of such techniques can reduce cost and effort, provide novel information, and expand existing observations by improving their context, accuracy, and completeness. In addition, we contend that use of airborne and satellite remote‐sensing data during site selection can improve the ecological representativeness of future experiments. We conclude by recommending a high level of communication and collaboration between remote‐sensing scientists and ecologists at all stages of global change experimentation.